2021
DOI: 10.37349/etat.2021.00049
|View full text |Cite
|
Sign up to set email alerts
|

The promising potential of piperlongumine as an emerging therapeutics for cancer

Abstract: In spite of the immense advancement in the diagnostic and treatment modalities, cancer continues to be one of the leading causes of mortality across the globe, responsible for the death of around 10 million patients every year. The foremost challenges faced in the treatment of this disease are chemoresistance, adverse effects of the drugs, and the high cost of treatment. Though scientific studies over the past few decades have foreseen and are focusing on the cancer-preventive and therapeutic potential of natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 222 publications
0
17
0
Order By: Relevance
“…A study by the same authors identified PL and four analogs as possessing senolytic activity (Wang et al, 2016 ). PL originates from the long pepper plant and has been studied for its anti‐cancer effects and ability to modulate signaling pathways influencing cell‐cycle regulation, nutrient signaling, and the immune response (Parama et al, 2021 ). A follow‐up study investigating senolytic targets of PL, found it binds to and promotes degradation of oxidation resistance 1 (OXR1) and to induce apoptosis (Zhang et al, 2018 ).…”
Section: Discovery Of the First Senolytic Drugsmentioning
confidence: 99%
“…A study by the same authors identified PL and four analogs as possessing senolytic activity (Wang et al, 2016 ). PL originates from the long pepper plant and has been studied for its anti‐cancer effects and ability to modulate signaling pathways influencing cell‐cycle regulation, nutrient signaling, and the immune response (Parama et al, 2021 ). A follow‐up study investigating senolytic targets of PL, found it binds to and promotes degradation of oxidation resistance 1 (OXR1) and to induce apoptosis (Zhang et al, 2018 ).…”
Section: Discovery Of the First Senolytic Drugsmentioning
confidence: 99%
“…Akt deactivation decreases cyclin D level and ceases the cell cycle at the G2/M phase, thus stopping tumor enlargement [ 28 ]. Additionally, the down-regulation of the genes fibronectin-1 (FN1), cadherin-2 (CDH2), catenin beta-1 (CTNNB1), and twist-related protein 1 TWIST1 is a well-known mechanism of PPL to control cancer cell metastasis [ 29 ].…”
Section: Anticancer Drugs For the Treatment Of Colon Cancermentioning
confidence: 99%
“…17−19 It has been shown to exert cytotoxic effects on nonsmall cell lung cancer (NSCLC) cells and enhance the efficacy of standard chemotherapy drugs. 20 Piperlongumine regulates the PI3K/ Akt/mTOR pathway and inhibits the expressions of ERK 1/2 and NF-κB in lung cancer cells. 21,22 However, its clinical application is limited by low efficacy and potential toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin, a natural compound found in turmeric (Curcuma longa), possesses notable anti-inflammatory, antitumor, and free radical-scavenging properties . In recent years, numerous preclinical and clinical studies have demonstrated the potential therapeutic value of curcumin against various diseases, including inflammatory bowel disease, arthritis, pancreatitis, chronic anterior uveitis, and certain types of cancer. Nevertheless, the clinical application of curcumin is significantly limited due to its high metabolic instability, low bioavailability, and rapid plasma clearance. , Studies have shown that the active methylene group of β-diketone moiety in the structure of curcumin contribute to its instability, rapid metabolism, and poor bioavailability. Piperlongumine, a natural alkaloid derived from Piper longum Linn ., has demonstrated promising antitumor effects and potential as a chemotherapeutic agent for lung cancer. It has been shown to exert cytotoxic effects on nonsmall cell lung cancer (NSCLC) cells and enhance the efficacy of standard chemotherapy drugs . Piperlongumine regulates the PI3K/Akt/mTOR pathway and inhibits the expressions of ERK 1/2 and NF-κB in lung cancer cells. , However, its clinical application is limited by low efficacy and potential toxicity. , Further research is needed to explore the potential of piperlongumine as a treatment option for lung cancer.…”
Section: Introductionmentioning
confidence: 99%